PENURUNAN KADAR FORMALIN DALAM IKAN ASIN TERI NASI MELALUI PERENDAMAN DALAM CUKA MAKAN - Amelia Handayani Burhan (JURNAL ILMU KESEHATAN BHAKTI SETYA MEDIKA, 2018)
Anchovy salted fish is relatively popular with the community, but there are still many that contain formaldehyde, especially in Yogyakarta. One effort can be made to reduce formaldehyde concentrations by soaking in organic acids. Vinegar is an organic acid that can be used to break formaldehyde bonds with protein in anchovy salted fish. The purpose of this study was to identify formalin and the effect of the concentration of vinegar on the formaldehyde in anchovy salted fish sold in the Yogyakarta Traditional Market. Sampling was conducted in 5 Yogyakarta Traditional Markets with 5 samples from 5 different markets in each market. Positive samples were soaked in vinegar solutions0, 2, 5, 10, 15 and 20%. Determination of formaldehyde concentration before and after soaking in vinegar solution was using the acidimetric method with HCl 1,0029 N standard solution and methyl red indicator. Based on the results of the formalin kit test, there were 84% of 25 samples is containing formaldehyde. Formaldehyde concentration in the sample before soaking was 12,642%. At 30 minutes soaking for concentrations of 0, 2, 5, 10, 15, and 20% for eating vinegar, the amount of formalin decrease in succession was 76.19; 88.10; 90,48; 95,24; and 97.62%.The higher the concentration of vinegar used, the more formalin that was successfully reduced from anchovy salted fish (Sig. <0.05).